Beginning Counselor Educators’ Experiences of Teaching Mentorship - Phillip L. Waalkes Dr.; Daniel Hall; Paula J. Swindle; Jaimie E. Stickl Haugen (Teaching and Supervision in Counseling, 2021)
Mentoring can positively impact counselor educators’ teaching in terms of self-efficacy and growth in skills. Yet, counselor educators have reported a desire for more mentoring in the development of their teaching. Utilizing consensual qualitative research methodology, we explored the teaching-specific mentorship of beginning counselor educators’ (N = 13) within their first two to four years as faculty. Emergent themes included mentoring structure such as mentors’ methods of providing mentorship, mentoring relationship dynamics such as relational supports and frustrations, and the positive and negative impacts of mentoring relationships. In addition to building rapport and strengthening mentees’ self-efficacy, mentors and mentees can develop intentional mentoring relationships with a comprehensive focus emphasizing the development of teaching knowledge and skills through practices such as teaching observation and feedback. Additionally, discussing the needs, goals, and expectations of both parties and the inherent power differential of the relationships can help focus the mentoring experiences.
Keywords: pedagogy; mentoring; teaching mentoring